Questions and Questioning Techniques: A View of Indonesian Students’ Preferences - Ragawanti, Debora Tri (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
This study investigated students’ preference on teacher’s questions and questionings techniques and more importantly on how they could facilitate or impede their learning. The results on teacher’s questioning techniques showed that random nomination was more preferred than pre-arranged format nomination. In addition, techniques of nominating volunteering students and of giving wait-time were disliked by most student-respondents. As for types of question, the yes/no question was favored by most of the respondents. Different from the yes/no question, the number of respondents leaning forward to the analysis question, questions about fact of life, and questions to state opinion did not show a significant difference from the number of those leaning against the same questions.